Effect of doping concentration on dual-mode LaVO4:Eu3+ luminescence thermometers. Issue 12 (15th June 2023) - Kolesnikov, Ilya E.; Mamonova, Daria V.; Kurochkin, Mikhail A.; Medvedev, Vassily A.; Kolesnikov, Evgenii Yu
Abstract: In recent years, we have witnessed tremendous progress in contactless thermal sensing because of the rapid development of luminescence thermometry. Although the thermometric performances of several luminescence thermometers were reported to be comparable with those of convenient contact thermal sensors, there is still room for further improvement. Majority of optical thermometers are based on a single temperature-sensitive luminescence parameter, whereas multiparametric readouts could broaden the working range and enhance the reliability of temperature measurements. Here, we report on a LaVO4 :Eu 3+ concentration series as dual-mode luminescence thermometers. The effect of the Eu 3+ concentration on structural, luminescence, and thermometric properties of the materials was studied in detail. Two dual-excited single band ratiometric strategies and monitoring spectral position of the LaVO4 charge transfer band provide accurate thermal sensing in a wide temperature range. The best thermometric performances of studied phosphors attain Sr = 2.3% K −1 and ΔT = 0.2 K at room temperature.